Measuring patient safety climate: a review of surveys. Issue 5 (29th September 2005) - Colla, J B; Bracken, A C; Kinney, L M; Weeks, W B
Abstract : Objective: Five years ago the Institute of Medicine recommended improving patient safety by addressing organizational cultural issues. Since then, surveys measuring a patient safety climate considered predictive of health outcomes have begun to emerge. This paper compares the general characteristics, dimensions covered, psychometrics performed, and uses in studies of patient safety climate surveys. Methods: Systematic literature review. Results: Nine surveys were found that measured the patient safety climate of an organization. All used Likert scales, mostly to measure attitudes of individuals. Nearly all covered five common dimensions of patient safety climate: leadership, policies and procedures, staffing, communication, and reporting. The strength of psychometric testing varied. While all had been used to compare units within or between hospitals, only one had explored the association between organizational climate and patient outcomes. Conclusions: Patient safety climate surveys vary considerably. Achievement of a culture conducive to patient safety may be an admirable goal in its own right, but more effort should be expended on understanding the relationship between measures of patient safety climate and patient outcomes.